Dorello's Canal for Laymen: A Lego-Like Presentation - Ezer, Haim; Banerjee, Anirban Deep; Thakur, Jai Deep; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective Dorello's canal was first described by Gruber in 1859, and later by Dorello. Vail also described the anatomy of Dorello's canal. In the preceding century, Dorello's canal was clinically important, in understanding sixth nerve palsy and nowadays it is mostly important for skull base surgery. The understanding of the three dimensional anatomy, of this canal is very difficult to understand, and there is no simple explanation for its anatomy and its relationship with adjacent structures. We present a simple, Lego-like, presentation of Dorello's canal, in a stepwise manner.Materials and Methods Dorello's canal was dissected in five formalin-fixed cadaver specimens (10 sides). The craniotomy was performed, while preserving the neural and vascular structures associated with the canal. A 3D model was created, to explain the canal's anatomy.Results Using the petrous pyramid, the sixth nerve, the cavernous sinus, the trigeminal ganglion, the petorclival ligament and the posterior clinoid, the three-dimensional structure of Dorello's canal was defined. This simple representation aids in understanding the three dimensional relationship of Dorello's canal to its neighboring structures.Conclusion Dorello's canal with its three dimensional structure and relationship to its neighboring anatomical structures could be reconstructed using a few anatomical building blocks. This method simplifies the understanding of this complex anatomical structure, and could be used for teaching purposes for aspiring neurosurgeons, and anatomy students.
Keywords: Dorello's canal; anatomy; 3D; skull base